Analysis of Waiting Time for Medication Services in the Pharmacy Installation of Mesra Hospital - Nailul Fithri Arrasily; Jasrida Yunita; Nofiyadi Nofiyadi (Journal of Education on Social Science (JESS), 2025)
Hospital pharmacy services are an integral part of the healthcare system, playing a crucial role in ensuring the availability of appropriate, safe, and timely medications for patients. One indicator of pharmaceutical service quality is the waiting time for medication services, which directly impacts patient satisfaction and the hospital's image. The Mesra Hospital Pharmacy Unit continues to face issues with waiting times for medication services that do not fully meet standards, particularly during peak service hours. This study aims to analyze waiting times for medication services, identify contributing factors, and formulate recommendations for improvement based on field conditions. The study used a qualitative approach with a case study design. Data were collected through in-depth interviews with pharmacy staff and management, observations of service flows, and a review of secondary data from wait time quality reports for the July–September 2025 period. Root cause analysis was conducted using Fishbone Analysisto identify human factors, work methods, infrastructure, and service management. The results showed that long waiting times were influenced by an imbalance in staff workload, delays in prescription input, limited space and compounding equipment, inconsistent implementation of standard operating procedures (SOP), and patient congestion at certain times. In conclusion, improvements to the workflow and management of pharmaceutical services are needed to reduce waiting times and improve service quality at Mesra Hospital.